Neotectonic transpressive zones in the Precordillera sur, central Andes of Argentina: a structural and geophysical investigation - Terrizzano, Carla Marina (2009)
On the flat-slab segment of the Central Andes of Argentina, the southern portion (31°30' - 33° SL) of the Precordillera is characterized by a singular Late Cenozoic tectonic style related to the tectonic inversion of paleotectonic anisotropics. Different scale, neotectonic NW trending deformation zones are described at this area. All these belts show me same structural style, defined by an en échelon array of morphotectonic features which indicate a left-lateral component of displacement under a transpressive regime. Oblique paleotectonic features seem to play a major role in the geometry and kinematics of Late Cenozoic deformation of the northern Precordillera Sur. In agreement with geological data, a tomography of electrical resistivity survey across one of these zones suggests a Quaternary reverse reactivation of a NW trending extensional paleotectonic fault.